Analisis Fluktuasi Muka Air dan Dasar Sungai Akibat Pasang Surut pada Muara Sungai - Melda Melda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to examine the influence of high tides on fluctuations in the speed of flow and water level of the river in the estuary palu. The method used in this study was simulation using HEC-RAS (Hydrologic Engineering Center-River Analysis System) software. This simulation was carried out with the topography of Palu river to downstream (estuary) as geometric input, flow discharge as upstream and tidal inputs as downstream inputs and sediment as input gradation granules. The simulation result of HEC-RAS program on fluctuations in flow speed and river water level in Palu river estuary is as follows the impact of tidal influence that occurs in palu river estuary along ± 912 m to upstream of the river at sp16 point. Changes in riverbed elevation in the estuary at the end of the simulation duration ranged from -0.265 m to -0.205 based on high tides at maximum duration. In conclusion, analysis of unstedy flow obtained the impact of tidal influences that occurred in the estuary sumgai Palu along ± 912 m to the upstream of the river. So it can be stated the relationship, that the greater the discharge flowing the higher the elevation of the tides produced. Keywords: Tidal, HEC-RAS, Estuary, River Discharge